Perioperative systemic treatments in renal cell carcinoma - Goswamy, Rohit; Kalemoglu, Ecem; Master, Viraj; Bilen, Mehmet Asim (Frontiers in Oncology, 2024)
In this review, we aim to provide a comprehensive assessment of the evolving landscape of the perioperative management in renal cell carcinoma (RCC), emphasizing its dynamic and intricate nature. We explore academic and clinical insights into the perioperative treatment paradigm of RCC. Up-to-date treatment options are discussed and the evolving role of neoadjuvant and adjuvant therapy in RCC is highlighted.